Personnel Practices and Regulation: How Firm-Provided Incentives Respond to Changes in Mandatory Retirement Law - Frederiksen, Anders; Manchester, Colleen Flaherty (Journal of Labor Economics, 2021)
We study how firms’ personnel practices react to labor market regulation. While a company is compelled to comply with a new law, what is the ripple effect of the change on existing personnel policies and practices? We provide evidence using passage of the Age Discrimination in Employment Act and nearly two decades of administrative data from a large US firm. In line with theory, we find a weakening of long-term implicit incentives and movement toward pay for performance. Furthermore, the data are consistent with the firm carefully managing its personnel practices according to economic principles to preserve incentives for employees.